2005
DOI: 10.1111/j.1742-1241.2005.00436.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the switch in the use of antihypertensive medications

Abstract: The present study was undertaken to explore factors associated with observance of prescribed antihypertensive medications. Secondary data analysis utilising ambulatory claims of the Taiwan National Health Insurance involved all initially treated hypertensive patients (n=565,048) from June 1, 1997 to June 30, 1998. The main outcome measure was the statistical analysis of factors prompting medication switch and dropout rates. The overall continuity rate was 51%. Specific continuity rates were 40% for calcium ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
0
9
0
1
Order By: Relevance
“…Similar database studies including pooled Italian, Swedish and Dutch cohorts reported a 9 month switching rate of 15.9% [30]. A historical analysis adopting the ambulatory claims of the Taiwan National Health Insurance found that the proportion of patients switching their antihypertensive agents ranged from 21-29% in a one-year follow-up period [16]. Our recent studies among Chinese hypertensive patients, including both new and follow-up clinic visitors in the years 2004-2007 [23,31], showed that 5.7% had their medication switched which is compatible with the low switching rate in the current study.…”
Section: Relationship To Literature and Explanationsmentioning
confidence: 88%
See 1 more Smart Citation
“…Similar database studies including pooled Italian, Swedish and Dutch cohorts reported a 9 month switching rate of 15.9% [30]. A historical analysis adopting the ambulatory claims of the Taiwan National Health Insurance found that the proportion of patients switching their antihypertensive agents ranged from 21-29% in a one-year follow-up period [16]. Our recent studies among Chinese hypertensive patients, including both new and follow-up clinic visitors in the years 2004-2007 [23,31], showed that 5.7% had their medication switched which is compatible with the low switching rate in the current study.…”
Section: Relationship To Literature and Explanationsmentioning
confidence: 88%
“…However, not all patients on pharmacotherapy receive the full potential benefit from treatment. Adverse effects of drugs or inefficacy of blood pressure control have been one major causes of switching of antihypertensive agents in clinical practice [16].…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicate that the side‐effect profiles of ARBs are much better than those of ACEIs and are similar to placebo 50 . It is tempting to speculate that the side effects of cough induced by ACEIs were more prevalent in Taiwan; although the reported incidence of cough as a side effect was 3% to 4%, it is estimated to be as high as 39% in female Taiwanese 12 , 41 . Better compliance and evidence‐based clinical trials may have contributed to the increased use of ARBs over ACEIs, despite the increased cost.…”
Section: Discussionmentioning
confidence: 99%
“…Кроме того, это может быть косвенным признаком низкой преем-ственности в работе специализированных учрежде-ний и первичного звена здравоохранения. Данное предположение подтверждают результаты тайвань-ского исследования, продемонстрировавшие то, что изменение клиники, где наблюдались пациенты, стало самым значимым фактором, ассоциированным с изменением АГТ [9]. Также высокая частота само-стоятельной смены препаратов пациентами КД может свидетельствовать о недостаточных усилиях врачей в отношении повышения приверженности пациентов.…”
Section: клиника и фармакотерапияunclassified